2014
DOI: 10.1007/s00247-014-3245-0
|View full text |Cite
|
Sign up to set email alerts
|

CT of the chest in suspected child abuse using submillisievert radiation dose

Abstract: The cornerstone of child abuse imaging is the skeletal survey, but initial imaging with radiographs may not demonstrate acute and non-displaced fractures, especially those involving the ribs. Given the high mortality of undiagnosed non-accidental trauma, timely diagnosis is crucial. CT is more sensitive in assessing rib fractures; however the effective radiation dose of a standard chest CT is high. We retrospectively identified four children (three boys, one girl; age range 1-4 months) admitted between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The authors found no significant difference between the sensitivity of skull radiographs and head CT with 3D reconstructions in identifying skull fractures. Sanchez et al reviewed the examinations of four children requiring CT of the chest in addition to the skeletal survey, and found that the average effective dose for reduced‐dose chest CT was 0.56 mSv.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found no significant difference between the sensitivity of skull radiographs and head CT with 3D reconstructions in identifying skull fractures. Sanchez et al reviewed the examinations of four children requiring CT of the chest in addition to the skeletal survey, and found that the average effective dose for reduced‐dose chest CT was 0.56 mSv.…”
Section: Resultsmentioning
confidence: 99%
“…In cases of infant death, if magnetic resonance imaging (MRI) is not possible for technical, or practical reasons (no MR unit accessible, personnel for MRI not available), PMCT is mandatory if available, as skeletal injuries or malformations are often difficult to see in a conventional autopsy [ 21 , 22 ]. Also, it must be noted that radiological examination of infant bodies can be used in non-forensic cases as the parents frequently will not agree to an autopsy.…”
Section: Pmctmentioning
confidence: 99%
“…The limitations of chest radiography for the investigation of rib fractures are recognised by experienced reporters, 18 and CT has been proposed as an improved method of rib fracture detection 19 . Three previous studies comparing CT with radiography for rib fracture detection have either been case series 20 in live children without autopsy correlation, 7 or underpowered with single-reporter bias 13 . Wootton-Gorges and colleagues 7 suggested that CT was superior for all rib fracture locations (anterior, lateral, and posterior), because only 79 (60%) of 131 fractures identified by use of CT were found by use of radiography in 12 live children, although only four children had complete CT scans of the chest and none had autopsy correlation.…”
Section: Discussionmentioning
confidence: 99%